Analisis Kesulitan Belajar Matematika Ditinjau Dari Kecemasan Matematika pada Kelas VII MTS SA Al Murtadho Kedungwaru - Muhammad Saifudin; Arum Dwi Rahmawati; Budi Sasomo (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This study aims to describe how difficulties are experienced by students from each level. The type of research conducted is qualitative descriptive. The subject of the study is a grade VII student at MTs SA Al Murtadho Kedungwaru. There are two instruments used in this study, the main instruments, namely the researcher and the supporting instruments, namely the mathematical anxiety questionnaire, the learning difficulty question test, and the interview guidelines for learning difficulties. The data analysis techniques used are data reduction, data presentation, and conclusion. The results showed that students who had low math anxiety tended to have difficulty solving problems that required variable determination. Students who have moderate learning difficulties tend to have difficulty in using principles and difficulties in solving problems that require the determination of variables. Students who experience high anxiety tend to experience all indicators of learning difficulties, ranging from difficulty in presenting concepts, difficulties in using principles, and difficulties in solving problems that require the determination of variables..